Surface waves on Saturn's dawn flank magnetopause driven by the Kelvin-Helmholtz instability - Masters, A. (2009)
Crossings of Saturn's magnetopause made by the Cassini spacecraft on 12, 13 and 17 March 2006 are analysed. During this period Cassini's trajectory was approximately parallel to the magnetopause boundary given by a model of the surface. Magnetic field and electron data are used to identify excursions into the magnetosheath bounded by crossings of the magnetopause current layer. Minimum variance analysis of the magnetic field vector measurements is used to determine the normal to the boundary for each crossing. The normals corresponding to the crossings oscillate about an average orientation that is consistent with the unperturbed normal predicted by the surface model. This reveals the presence of regular boundary waves with a direction of propagation found to be within 24° of Saturn's rotational equator. Two categories of boundary wave are identified: the first with a period of the order of hours, and the second with a period of 45±9 min. Based on the propagation direction and a comparison of magnetospheric and magnetosheath magnetic fields, we conclude that both types of wave were driven by the Kelvin–Helmholtz instability. The observed boundary perturbations are consistent with a superposition of different types of surface wave activity.